Flow-Rate-Regulated Co-Precipitation via Peristaltic Pump for Controlled Nucleation and Morphology of ZnO Nanorods - Thathit Suprayogi; Samsul Arifin; Sudarman Rahman; Mu'afa Purwa Arsana; Rokiy Alfanaar; Awalul Fatiqin; Yahya Febrianto (JPSE (Journal of Physical Science and Engineering), 2024)
This study presents a flow-rate-regulated co-precipitation method for synthesizing ZnO nanoparticles using a peristaltic pump to enhance control over nucleation and growth processes. The primary objective was to investigate the effect of controlled reactant delivery on the structural and morphological properties of ZnO nanoparticles. A peristaltic pump system was calibrated to provide a stable and continuous flow of the precipitating agent, achieving an average flow rate of 93.39 ± 1.39 µL/s with high linearity (R² = 0.99946). ZnO nanoparticles were synthesized under controlled conditions and characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD results confirmed the formation of a single-phase hexagonal ZnO structure with high crystallinity and an average crystallite size of 55.98 ± 8.35 nm. SEM analysis revealed the formation of nanorod structures with relatively uniform morphology. The improved uniformity is attributed to stable supersaturation conditions enabled by precise flow-rate control. These findings demonstrate that flow-rate regulation is a critical parameter in co-precipitation synthesis and offers a simple, cost-effective strategy for improving reproducibility and structural control in nanoparticle fabrication.